Diagnosis of Alzheimer's Disease in Developed and Developing Countries: Systematic Review and Meta-Analysis of Diagnostic Test Accuracy - Chavez-Fumagalli, Miguel A. (2021)
This study was supported by the Consejo Nacional de Ciencia, Tecnologia e Innovacion y Tecnologia (CONCYTEC) and the Fondo Nacional de Desarrollo Cientifico, Tecnologico y de Innovacion Tecnologica de Peru (FONDECYT). Contract Nr. 24-2019. We would like to thank Dr. Maximo Rondon and Dra Karina Rosas and theVicerrectorado de investigacion for providing substantial support to the Laboratory of Genomics and Neurovascular Diseases to carry out this work.